Event related desynchronization: use as a neurophysiologic marker is restricted - Turp Gölbaşı, Bilge; BAŞAR, EROL (Springer, Van Godewijckstraat 30, 3311 Gz Dordrecht, Netherlands, 2014)
The present research aims to show that the occurrence of alpha blocking or event-related desynchronization (ERD) strongly depends on the amplitude and also on the phase angle of alpha activity at the stimulus onset. Simple visual stimulation was presented to 17 healthy subjects during EEG recording. An O-2 electrode was used for analysis with a 32 channel EEG sampling system. We used a segmentation of raw data in order to obtain the evoked potential. Prestimulus and poststimulus activities were filtered in the alpha (8-13 Hz) frequency band. Later, four different events (blocked, time-locked, phase-locked, and eliminated) were separately averaged. Phase-locked sweeps were determined by application of inter-trial coherence analysis. The evaluation of the data shows that "time-locked and phase-locked sweeps" were the dominating pattern and not "the blocked pattern", which occurred only when the prestimulus alpha was high. In the analyses of EEG-EP sweeps, only 22 % of epochs showed (ERD). The ANOVA revealed significant differences between four different alpha responses (F(3,48) = 11.175; p < 0.001). Furthermore, alpha oscillations in time-locked responses were significantly higher than blocked (p < 0.0001). The analyses clearly demonstrate that important precaution is needed when using the ERD as a cognitive or pathological marker.
Keywords: EEG; ERD; Evoked potential; Alpha; Oscillation activity; Occipital; Healthy subjects; Auditory Oddball Task; Prestimulus Alpha-Activity; Eeg Alpha; Oscillations; Potentials; Stimulation; Responses; Dynamics; Coherence; Phase